KEPEMIMPINAN PEMUDA KRISTEN: SUATU KAJIAN LITERATUR TENTANG PEMBINAAN GENERASI PEMIMPIN BERETIKA KRISTIANI - Yohanes Yohanes; Nopiani Rangan, Marthina Kanan, Selvi Arruan, Sartika Elma (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This research is a literature review aimed at investigating and summarizing the understanding of Christian youth leadership with a focus on nurturing an ethical Christian leader generation. Christian youth leadership is the subject of this research due to its crucial role in shaping the direction and values that will guide the church and society in the future. Through literary analysis, this study explores concepts of Christian youth leadership grounded in Christian teachings. The literature review encompasses key aspects such as character, values, ethics, and social responsibility that form the foundation of ethical Christian leadership. Additionally, the research explores various mentoring strategies and methods that have been proposed or applied to advance an integrity-driven generation of Christian leaders committed to Christian values. The results of this research are expected to provide a profound insight into the challenges and opportunities in shaping Christian youth leadership that is not only effective organizationally but also rooted in Christian moral and spiritual values. The implications or expectations of these findings can guide church leaders, educators, and mentors of Christian youth in their efforts to develop and nurture a generation of leaders capable of making a positive impact in an ever-changing societal context.